Do executive functions predict outcome in remitted bipolar patients? A case control study - Raga Sandhya Gandi; G Prasad Rao; Venugopal Duddu (Telangana Journal of Psychiatry, 2016)
Background: Bipolar disorder patients have cognitive deficits even during periods of remission particularly in domains of executive functions and verbal memory that contribute to poor functional recovery. The present study aims to identify the executive function deficits in bipolar patients in remission, and its influence on overall functioning. Methods: Twenty consenting patients with diagnosis of a bipolar disorder (YMRS scores<11 and HRSD scores<8) and twenty healthy controls satisfying the inclusion and exclusion criteria were recruited for the study. All participating subjects were administered the Color Trail test, Stroop test, fluency test and Tower of London test. Functioning was rated on Global assessment of functioning scale. Results: Cases and controls were comparable with respect to socio-demographic data. Remitted bipolar patients performed significantly worse than controls on, Fluency test, Color Trail test, and Stroop (C-W) scores and had significantly lower GAF scores compared to healthy controls (p<0.05). In the multiple regression analysis, executive functions contributed to 10.9% of the variance in GAF scores (after controlling for illness duration). Conclusion: Remitted Bipolar disorder patients have significantly more executive dysfunction than healthy controls and executive functions significantly predict global functioning.